A reversed genetic approach reveals the coenzyme specificity and other catalytic properties of three enzymes putatively involved in anaerobic oxidation of methane with sulfate. (29th April 2014) - Kojima, Hisaya; Moll, Johanna; Kahnt, Jörg; Fukui, Manabu; Shima, Seigo
Summary Consortia of anaerobic methanotrophic (ANME) archaea and delta‐proteobacteria anaerobically oxidize methane coupled to sulfate reduction to sulfide. The metagenome of ANME‐1 archaea contains genes homologous to genes otherwise only found in methanogenic archaea, and transcription of some of these genes in ANME‐1 cells has been shown. We now have heterologously expressed three of these genes in Escherichia coli, namely those homologous to genes for formylmethanofuran : tetrahydromethanopterin formyltransferase, methenyltetrahydromethanopterin cyclohydrolase (Mch) and coenzyme F420‐dependent methylenetetrahydromethanopterin dehydrogenase (Mtd), and have characterized the overproduced enzymes with respect to their coenzyme specificity and other catalytic properties. The three enzymes from ANME‐1 were found to catalyse the same reactions and with similar specific activities using identical coenzymes as the respective enzymes in methanogenic archaea, the apparent Km for their substrates being in the same concentration range. The results support the proposal that anaerobic oxidation of methane to CO2 in ANME involves the same enzymes and coenzymes as CO2 reduction to methane in methanogenic archaea. Interestingly, the activity of Mch and the stability of Mtd from ANME‐1 were found to be dependent on the presence of 0.5–1.0 M potassium phosphate, which suggested that ANME‐1 archaea contain high concentrations of lyotropic salts, presumably as compatible solutes.